Analysis of structural elements and energy consumption of school building stock in Cyprus: Energy simulations and upgrade scenarios of a typical school - Katafygiotou, Martha; Serghides, Despina Kyprianou (My University, 2014)
Structural and energy consumption details from the secondary school buildings of Cyprus are presented in this paper. The study identifies the prevailing building practices in schools' construction in the three climatic zones of Cyprus, coastal, inland and mountainous. Furthermore the construction details of schools are compared with their energy consumption. In this questionnaire survey 24 schools were responded with a completed profile and represent the 15% of schools and through further interviews and in situ visits more data are collected from a percentage of 60% of the secondary schools in Cyprus. The analysis through questionnaire results conclude to significant findings which are very revealing and may be used as a preliminary study on energy upgrading of schools. Furthermore through a statistical study the construction details of the mean typical secondary school building in Cyprus are also derived. A case study with simulations for the energy performance of a representative typical school building is also developed. Variables of the building elements are examined through parametric simulations using the software iSBEMcy. This is the official governmental software used for the categorization of energy efficiency in buildings and the calculation of CO2 emissions according to the European Directive 2002/91/EC. Based on the energy categorization of the building six retrofitting scenarios are studied in simulations.
Keywords: Building stock; Energy consumption; Energy simulations; Retrofitting; Typical secondary school